Zero to One AWS Lambda with SAM and Python in One Hour - Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2021)
Zero to One: AWS Lambda with SAM and Python in One Hour. Learn to use AWS Cloud9 to develop serverless applications with Python and SAM (Serverless Application Model) Topics include: * Building a Lambda inside of Cloud9 * Deploying a containerized service to Amazon ECR and AWS Lambda * Invoking API Gateway based AWS Lambda services using sam invoke and AWS Cloud9.